Water, Sanitation, Hygiene (Wash) Interventions To Reduce Open Defecation Habit: A Structural Equation Modeling (SEM) Approach - Aurora, Wahyu Indah Dewi; Darmawan, Armaidi; Kusdiyah, Erny; Nuriyah, Nuriyah; Maria, Ima (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Open defecation and other poor sanitation and hygienic practices create major public health problems in many developing nations. Improving community health and well-being depends on attending to these problems. Using partial least squares structural equation modeling (PLS-SEM), this study aims to investigate the links between Water, Sanitation, and Hygiene (WASH) parameters and open defecation behavior in riverbank villages. Method: Environmental observations combined with structured questionnaires was used in a cross-sectional survey. Convenience sampling helped participants to be gathered; PLS-SEM data analysis was used to investigate the intricate connections between WASH factors and open defecation behavior. Result: results show that there is no statistically significant relationship between open defecation practices and water (coefficient = -0.128, p = 0.355), sanitation (coefficient = -0.493, p = 0.861), income (coefficient = -0.030, p = 0.675), or education (coefficient = 0.067, p = 0.377). Furthermore, there is no significant link between open defecation practices and water (coefficient = -0.009, p = 0.911) and sanitation (coefficient = 0.058, p = 0.479) moderating effects of hygiene. Conclusion: Effective reduction of open defecation hinges on comprehensive WASH interventions that combine improved sanitation infrastructure with hygiene promotion and community involvement. Prioritizing hygiene education and fostering community ownership are essential for sustainable public health improvements. (rekomendasi dari hasil untuk future persepective )